Ipv6 address planning designing an address plan for the future - Coffeen, Tom (O'Reilly Media, 2015)
If you're ready to join the move to IPv6, this comprehensive guide gets you started by showing you how to create an effective IPv6 address plan. In three example-driven sections-preparation, design, and maintenance-you'll learn principles and best practices for designing, deploying, and maintaining an address plan far beyond what's possible with IPv4 networks. Enterprise IT network architects, engineers, and administrators will see firsthand how IPv6 provides opportunities for creating an operationally efficient plan that's scalable, flexible, extensible, manageable, and durable.